Produção e qualidade nutricional da forragem da aveia preta e do azevém em diferentes estandes populacionais e fases de desenvolvimento da para produção de pré-secado - Dochwat, André (2019)
The use of winter cereals for the purpose of pre-dried silage has become a tool to maintain the productivity of the intensive livestock system. However, the quantity and the quality of forage produced by winter cereals are dependent on several factors, among which the variability among species, among genotypes of the same species, and especially the management conditions employed in the crop. Four experiments were carried out to evaluate the productivity and the nutritional value of black oats (Embrapa 139 cv.) And ryegrass (Winter Star cv.) At different sowing densities and different harvest times in the vegetative stage in the Guarapuava-PR region, where in experiment 1, in the evaluation of black oats (Avena strigosa) cv. EMB 139 was used sowing densities of 40 and 80 kg ha-1 and in experiment 2, in the evaluation of ryegrass (lolium multiflorum) cv. Winter Star was used sowing densities of 20, 40 and 80 kg ha-1, in experiment 3 and 4 were used three harvest times, all experiments with two successive cuts. Experiment 1: The cultivated black oats with sowing density of 40 kg ha-1 increased the number of m2-1 tillers and plant-1 tillers, in addition to improving the in situ dry matter digestibility of the whole plant, without causing reduction of dry biomass production per unit area. Successive cuts in black oats determine variations in dry biomass production and forage quality. In the first cut we have lower yields of dry biomass, but with superiority in the nutritional quality of the forage in relation to the second cut. Experiment 2: The sowing density of 20 kg ha-1 in ryegrass culture due to greater participation of green leaves in the physical composition of the plant (50.52%) and higher in situ dry matter digestibility of the whole plant (84.81%), without generating a reduction in dry biomass production per unit area (6.087 kg of dry biomass ha-1). The first ryegrass harvest season resulted in a higher leaf greenness and a better leaf / stem ratio of 58.62% and 3.41, respectively, as well as greater digestibility of green leaves (77.26%) and stem (80, 82%). Experiment 3: The greatest participation of green leaves was observed in season 1 with 60.98%, but with each harvest decreasing gradually and the in situ digestibility of the green leaves followed the same trend of reduction and the content of FDA increased with each harvest arriving to 34.7% in season 3. It is recommended to harvest the black oat forage in the first harvest season for both cuts, because it presented a better nutritional quality that compensates the loss in productivity. Experiment 4: Season 1 shows higher crude protein contents 20.91% and greater in situ digestibility of whole plant 81.95%. In the comparison between the cuts, the first cut had the highest production of dry biomass kg ha-1 with 4258 kg, had a greater participation of green leaves 58.98% and smaller participation of high 20.93% and of senescent leaves 9.95% and consequently presented a better leaf / stem ratio 3.00. The digestibility of the whole plant, the green leaves and the stem in the first cut was superior to the second cut with 85.87%; 71.65%; 80.60% respectively. The ryegrass harvest is recommended in the first harvesting season, as the harvest delay generated a higher productivity per unit area, but with a lower nutritional quality.